Analisis Yuridis Penerapan Asas Ultimum Remedium guna Mewujudkan Kepastian Hukum dalam Tindak Pidana Perpajakan - Taufik Taufik; Vitra Yozi; Febby Angelia; Lisda Apriliani Sobirin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to analyze the application of the ultimum remedium principle in tax crimes and its relevance in establishing legal certainty in Indonesia. The main focus of the research is directed toward the juridical position of this principle, the normative and practical obstacles in its implementation, and the need for reformulation of tax law policies. This research employs a normative legal method with a qualitative approach through the statute approach, conceptual approach, and case approach. Data sources were obtained from statutory regulations, court decisions, scholarly literature, and official documents, which were analyzed descriptively using systematic, historical, and teleological interpretation. The findings reveal that the ultimum remedium principle has not been optimally implemented due to the absence of explicit regulations prioritizing administrative sanctions before the use of criminal law. This condition creates ambiguity in distinguishing administrative violations from tax crimes, disparities in law enforcement, and weak protection of taxpayers’ rights. The study recommends regulatory harmonization, the formulation of national operational guidelines, and stronger coordination among law enforcement institutions to ensure that criminal law is genuinely applied as a last resort in a proportional and just manner.